Impact of persulphate mixed with paper sludge on activated sludge dewaterability. (19th June 2020) - Wang, Sen; Cheng, Saige; Xiao, Xueli; Lai, Fan
Abstract: FeSO4 was used to activate K2 S2 O8 mixed with paper sludge to condition activated sludge, and its effect on sludge dewaterability was investigated. Interaction effects of various parameters on sludge dewaterability were investigated and analysed by considering the moisture content of cake, specific resistance to filtration (SRF) and capillary suction time (CST) as indicators and the Box–Behnken design of response surface methodology (RSM). Results indicated that the moisture content of cake, SRF and CST decreased from 74.52 to 69.57%, 25.39 × 10 12 to 11.80 × 10 12  m/kg and 199.8 to 146.4 s, respectively, under optimal conditions. RSM results presented that only 0.13% of the response values cannot be interpreted with this model, and the three‐factor interaction was observed to be significant. Additionally, sludge dewaterability mechanism observed that K2 S2 O8 mixed with paper sludge used the strong oxidising properties of SO4 − to crack sludge flocs. Fine fibres and calcium carbonate in the paper sludge played important roles as the skeleton support in the sludge filtration process, and the internal moisture was rapidly eliminated.